Quality control and safety management of oil and gas pipelines during its whole life cycle - Changliang JIANG (You-qi chuyun)
The development history and technical change of oil and gas pipeline quality management in China were reviewed focusing on pipeline quality control in the whole life cycle, on the basis of quality improvement of oil and gas pipelines in the construction period. Starting with the construction of the "8.3" pipeline, China's long-distance oil and gas pipeline construction has undergone four major stages of leap-forward development, forming a new pattern of oil and gas strategic channels "running north-south, crossing east-west, covering the whole country and connecting overseas". With the extensive application of automatic and intelligent technologies, the construction level and engineering quality of pipelines have been significantly improved. With the mature application of whole life cycle risk assessment, monitoring and inspection, integrity evaluation and other integrity management technologies, the operational risks of pipelines have been effectively controlled. With the improvement of welding technology and construction quality, the promotion and application of digital technology, the improvement of the whole life cycle integrity technology system, and the breakthrough in the failure mechanism of high-grade steel pipelines, the intrinsic safety and the quality and safety management level of oil and gas pipeline in the whole life cycle have been effectively improved. Besides, analysis was conducted on the challenges faced by the construction quality and operation safety of oil and gas pipelines. In addition, the logical relationship of mutual undertaking and support between quality, risk and safety of pipelines in the whole life cycle was discussed, by considering the key quality control factors, such as the causes of girth weld defects, full-automatic welding and performance improvement. Moreover, the essential relationship among quality control, risk identification and safety management was analyzed based on the construction and operation practice of the China-Russia Eastern Gas Pipeline. Then, a new construction quality and operation safety model with "quality control as the basis, total-factor management as the core and enhanced whole life cycle risk resistance" was put forward. Finally, the technical direction of quality control and safety management of oil and gas pipelines was prospected based on the application of "Industrial Internet +" and digital technology.